Pemberdayaan Perempuan Dalam Pembangunan Pariwisata di Kabupaten Pangkep: Women's Empowerment in Tourism Development in Pangkep Regency - Muhammad Salim, Muhammad Arfin; Ery, Anda Prasetyo (PADAIDI: Journal of Tourism Dedication, 2024)
The Tourism sector is one of the developing sectors in Indonesia that can improve the economy of a country or region. Tourism is currently growing, which can open up vast employment opportunities. Women's empowerment through the community is a forum for developing the economy of Panaikang village, especially the introduction to tourism itself and its elements. One of them is the role of women in capacity building and community understanding of the benefits of tourism. Community service is packaged as technical guidance on women's war in developing villages and poverty alleviation in Panaikang Tourism Village. This technical guidance includes providing material about the Tourism Village to improve the community's standard of living around the Panaikang Tourism Village. The results of this service activity day showed that the community was very enthusiastic and actively participated in the activity. This activity has a significant impact on the community, especially in terms of gender equality and the role of women in poverty alleviation in Panaikang Village.